Concepts to Calculate Equilibrium Exchange Rates: An Overview - Ronald MacDonald (Deutsche Bundesbank, 2000)
In this paper we present a critical overview of differnt methods of constructing an equilibrium exchange rate. The recent literature on purchasing power parity (PPP) indicates that on its own PPP is not a good vehicle for defining an equilibrium exchange rate. Rather, we argue that the latter can only be recover from a model in which the real determinants of exchange rates are explicitly modelled. The advantages and disadvantages of various such models are discussed. In particular, the internal-external balance approach to defining an equilibrium real exchange rate is disccused, and this method is compared to the so-called behavioural equilibrium approach. Finally, an approach which uses purely time series methods to construct an equilibrium exchange rate is also discussed.
Keywords: F31; 330; Equilibrium Exchange Rates; Purchasing Power Parity; Real Exchange Rate Models; Wechselkurstheorie; Gleichgewicht; Kaufkraftparität; Ökonometrisches Modell; Theorie